Effect of Supplementation of Eucalyptus (Eucalyptus globulus) Leaf Powder in Diet Containing Phytase Enzyme on Performance of Commercial Laying Hens - Kaur, Manveen; Kumar, Ripusudan; Mondal, Bidhan C.; Siddiqui, Rukkiya; Kumar, Ashoka; Palod, Jyoti; Manjulata; Kumar, Sudhir (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A feeding trial was conducted to discern the influence of dietary incorporation of eucalyptus (Eucalyptus globulus) leaf powder on nutrient utilization, egg quality, and haemato-biochemical parameters of White Leghorn laying hens for 12 weeks. A total of 72, twenty eight days old laying hens were randomly assigned into four treatment groups, with 18 hens per treatment having three replicates of 6 birds each. Four treatment groups were control (T1): basal diet and Treatment T2, T3, and T4 with the incorporation of 0.30, 0.45, and 0.60 % eucalyptus leaf powder, respectively, in a basal diet containing phytase @250 FTU/kg feed. Results showed a significant (p<0.05) increase in egg production in the group T2 compared to other treatment groups. There was no significant (p ≥0.05) effect on feed intake, feed conversion ratio, and nutrient utilization among various treatment groups. The eggshell quality, egg albumen, and yolk traits parameters did not differ significantly among treatment groups except shell thickness. The hematological values, i.e., hemoglobin, total erythrocyte count (TEC), and total leukocyte count (TLC) showed significant improvement (p<0.05) in T3 and T4 as compared to the control and T2 group, but no statistical differences were noted in packed cell volume (PCV), mean corpuscular haemoglobin (MCH), mean corpuscular volume (MCV) and mean corpuscular haemoglobin concentration (MCHC). There were no significant differences in serum biochemical attributes among the treatment groups, but a considerable decrease in level of serum cholesterol and triglycerides was observed with an increasing level of eucalyptus leaf powder in diet. Similarly, glucose concentration differed significantly among treatment groups being lowest in T3 group.